Final answer:
To simplify the expression (x - 2)(-2x² - 4x + 6), multiply each term in the first expression by each term in the second expression and combine like terms. The simplified expression is -2x³ - 2x - 12.
Step-by-step explanation:
To simplify the expression (x - 2)(-2x² - 4x + 6), we can use the distributive property. Multiply each term in the first expression, x - 2, by each term in the second expression, -2x² - 4x + 6, and then combine like terms.
Let's multiply:
- x * -2x² = -2x³
- x * -4x = -4x²
- x * 6 = 6x
- -2 * -2x² = 4x²
- -2 * -4x = 8x
- -2 * 6 = -12
Now let's combine like terms:
- -2x³ + 4x² + 6x - 4x² - 8x - 12
- -2x³ + (4x² - 4x²) + (6x - 8x) -12
- -2x³ - 2x - 12
So, the simplified expression is -2x³ - 2x - 12.